lea.online - Software Applications for Individuals with Low Literacy - Küster, Jan (Electronic Communications of the EASST, 2025)
In 2018, there were an estimated 6.2 million people between the ages of 18 and 64 with low literacy skills in Germany. The ”lea.online” project designed and implemented a software system with multiple applications in order to gain access to this otherwise closed field and to conduct further research of the underlying competency model. This work presents the principal aspects of the research and development project and the challenges involved. It highlights the relationships between the domain of basic education and software engineering. It also sheds light on issues related to publicly funded software engineering, software architecture, outsourcing, documentation, accessibility, legal implications and sustainability.